CHEMICAL AND SENSORY CHARACTERISTICS IN THE SELECTION OF BOURBON GENOTYPES - Ferreira, Andre Dominghetti; Abrahão, Juliana Costa de Rezende; Carvalho, Gladyston Rodrigues; de Carvalho, Alex Mendonça [UNESP]; Andrade, Vinicius Teixeira; Gonçalves, Flavia Maria Avelar; Malta, Marcelo Ribeiro (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2021)
The evaluation of coffee quality in Brazil for commercialization is conducted mainly through sensory analysis, also known as the cup test, in which professional tasters evaluate and score various attributes. The adoption of chemical methods could complement the sensory classification of beverages, if correlations between these chemical and sensory analyses exist, making classification less subjective. This work aimed to identify the relationships between the chemical and sensorial traits of coffee-beverage quality and to evaluate the use of these traits as criteria for the selection of Bourbon cultivars. Twenty coffee genotypes from the first three harvests across five municipalities of the state of Minas Gerais, Brazil were evaluated. The genotypic values, predicted for each genotype, were used to determine the index based on the sum of ranks from Mulamba and Mock. The genetic correlations among the evaluated traits were also estimated. The presented evaluations were not able to efficiently detect genetic and phenotypic relationships between the chemical and sensorial characteristics of drink quality, but as selection criteria for generation advancement in the beverage quality, it is possible to use these characteristics. Bourbon Amarelo LCJ 9-IAC, Bourbon Amarelo-Procafé, Bourbon Amarelo-Boa Vista, Bourbon Vermelho-São João Batista, and Bourbon Amarelo-Samambaia were the genotypes with the most promising cup quality in the studied regions. Through the selection of these five genotypes, the selection gain was 1.65% for sensory score for beverage quality, when the interaction among the studied environments was removed. The heritability was 92% for improving this trait.
Keywords: BLUP; Coffea arabica; Genetic correlation; Genetic improvement; Simultaneous selection